The Association Between Embryo Quality, Number of Transferred Embryos and Live Birth Rate After Vitrified Cleavage-Stage Embryos and Blastocyst Transfer - Zhu, Qianqian; Lin, Jiaying; Gao, Haoyuan; Wang, Ningling; Wang, Bian; Wang, Yun; Kuang, Yanping (Frontiers in Physiology, 2020)
Objective: The single-embryo transfer (SET) is the recommended approach to improve the live birth rate and reduce the complications related with multiple pregnancies. However, the physicians generally chose to transfer two embryos when the embryo quality decreased. The effect on the in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) outcomes following the transfer of a poor quality embryo along with a good quality embryo has been explored. But previous studies were limited by the fresh embryo transfer cycles, or the small sample size. Methods: A retrospective cohort study was performed among 26676 women undergoing first frozen embryo transfer (FET) from January 2011 to December 2017. Patients were grouped into five subgroups, including single embryo transfer (SET) with one good quality embryo (GQE), SET with one poor quality embryo (PQE), double embryos transfer (DET) with two GQE, DET with one GQE plus one PQE, and DET with two PQE. Multivariable logistic regression models were performed after controlling for other potential confounders to estimate the effect of number and quality of transferred embryos on pregnancy outcomes. Result: Although the live birth rate was significantly higher after DET-GQE+PQE compared with SET-GQE for cleavage stage embryo transfer (37.25% vs. 25.55%), no significant difference was found between DET-GQE+PQE and SET-GQE for blastocyst transfer (53.76% vs. 42.99%). However, the DET-GQE+PQE also had the highest multiple live births in both cleavage stage embryo transfer (8.70%) and blastocyst transfer (17.29%). The live birth rate after SET-PQE significantly decreased in comparing with SET-GQE (cleavage-stage embryo transfer: 12.16% vs. 25.55%; blastocyst transfer: 29.56% vs. 42.99%); and significantly increased after DET-2GQE compared with SET-GQE (cleavage-stage embryo transfer: 45.73% vs. 25.55%; blastocyst transfer: 60.31% vs. 42.99%). The live birth rate was also not different between DET-2PQE and SET-GQE for cleavage-stage embryo transfer and blastocyst transfer (cleavage-stage embryo transfer: 32.89% vs. 25.55%; blastocyst transfer: 46.25% vs. 42.99). Conclusions: In order to minimize the risk of multiple births, the data from this study did not support transferring DET with a GQE plus a PQE compared with SET with a GQE, especially for blastocyst transfer.